The vulnerabilities of premature children: home and institutional contexts - Rosane Meire Munhak da Silva; Adriana Zilly; Ana Paula Contiero Toninato; Letícia Pancieri; Maria Cândida Carvalho Furtado; Débora Falleiros de Mello (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze situations in which premature children are vulnerable in home care, in the first six months after hospital discharge. Method: Qualitative study, from the perspective of philosophical hermeneutics, carried out in a Brazilian city on the border. In-depth interviews were conducted, with a data analysis considering the method of interpretation of meanings. 18 mothers of premature children discharged from a hospital unit participated. 25 home visits and 56 calls were made. Results: The reports from the mothers express situations of vulnerability, concerns, needs for care, singularities of the development of the premature baby, and repercussions of institutional routines in home care. Final considerations: There are vulnerable circumstances in prematurity that reaffirm interconnected individual, social, and institutional dimensions. It is important to highlight that the institutional dimension involves the responsibility of health professionals not to increase individual and social vulnerabilities, but to promote care and seek to reduce situations that generate risks, uncertainties, concerns, and damages.